Penentuan Waktu Istirahat Untuk Meminimalisir Kelelahan Petani Menggunakan Metode Fisiologi - Putri Widia Agustina; Meri Andriani; Dewiyana (CV. ALIM'SPUBLISHING, 2023)
The work of farmers is prone to the risk of health problems such as pain in the joints and fatigue. The research problem is that farmers complain of rapid fatigue, so the purpose of the study is to determine the physiological workload on rice farmers when planting rice and determine the best time for farmers. Methods used are Cardiovascular Load (%CVL) and Energy Consumption to determine the weight of the workload of farmers, and rest time to determine the length of rest. Results and discussion, %CVL is 7 people with action no fatigue and 46 people with action needed improvement. Energy consumption is the smallest percentage of 4.14 kcal / minute with a mild classification and the largest percentage of 6.14 kcal / minute with a moderate classification. In the second measurement, the smallest percentage was 4.49 kcal/min with a mild classification, and the largest percentage was 6.90 kcal/min with a moderate classification. In the third measurement, the smallest percentage was 3.96 kcal/min with a mild classification, and the largest percentage was 6.39 kcal/min with a moderate classification. The smallest rest time was 12.65 minutes and the largest rest time was 120.39 minutes. In conclusion, the mean %CVL was 13.21% with no fatigue, 86.79% with improvement needed. Average energy consumption with mild classification with a percentage of 4.21% and moderate classification with a percentage of 6.26%. The smallest rest time is 12.65 minutes while the largest is 120.39 minutes